Cardiorenal syndrome: The emerging role of protein-bound uremic toxins - Lekawanvijit S. (Lippincott Williams and Wilkins, 2015)
Cardiorenal syndrome is a condition in which a complex interrelationship between cardiac dysfunction and renal dysfunction exists. Despite advances in treatment of both cardiovascular and kidney disease, cardiorenal syndrome remains a major global health problem. Characteristic of the pathophysiology of cardiorenal syndrome is bidirectional cross-talk; mediators/substances activated by the disease state of 1 organ can play a role in worsening dysfunction of the other by exerting their biologically harmful effects, leading to the progression of the syndrome. Accumulation of uremic toxins is a hallmark of renal excretory dysfunction. Removal of some toxins by conventional dialysis is particularly problematic because of their high protein binding. In this review, we demonstrate that protein-bound uremic toxins may play an important role in progression of cardiovascular disease in the setting of chronic kidney disease. The highly protein-bound uremic toxin indoxyl sulfate has emerged as a potent toxin adversely affecting both the kidney and heart. Direct cardiac effects of this toxin have been recently demonstrated both in vitro and in vivo. Specifically, potent fibrogenic and prohypertrophic effects, as well as oxidative stress-inducing effects, appear to play a central role in both renal and cardiac pathology. Many of these adverse effects can be suppressed by use of a gut adsorbent, AST-120. Potential mechanisms underlying indoxyl sulfate-induced cardiorenal fibrosis are discussed. Future research and clinical implications conclude this review. © 2012 American Heart Association, Inc.